Effects of Treadmill Exercise on Sexual Behavior and Reproductive Parameters in Chronically Stressed-Male Rats - Kelestimur, Haluk; Bulmus, Ozgur; Serhatlioglu, Ihsan; Ercan, Zubeyde; Kaya, Seyma Ozer; Yardimci, Ahmet; Canpolat, Sinan (Acad Sciences Czech Republic, Inst Physiology, 2021)
Exposure to chronic stress stimulates the hypothalamic-pituitary adrenal (HPA) axis and then simultaneously inhibits hypothalamic-pituitary-gonadal axis (HPG) axis activity. The inhibition formed by the HPA axis is the main mechanism of action of stress on reproductive function. HPG axis activity is known to be changed by various factors, including exercise. Exercise has been found to have a number of positive effects on sexual behavior, reproductive hormones, and sperm parameters in studies with animal models for many years. The main aim of this study is to investigate the effects of chronic treadmill exercise on chronically stressed-male rats' sexual behavior, reproductive hormones, and sperm parameters. A total of 40 sexually adult male rats were randomly and equally divided into four groups as control, stress, exercise, and stress+exercise. Animals in the exercise group were subjected to the chronic treadmill exercise (moderate intensity) for 33 days with a periodic increase in speed and duration. Animals in the stress group were exposed to restraint stress for 1 h, 2 h, and 3 h during the first, second and third 15 days respectively. Sexual behavior parameters, hormone measurements, and sperm parameters were evaluated. The main effects of chronic exercise on sexual behavior were centered on a significant increase in the ejaculation frequency (EF) in the stress+exercise group. Also, sperm concentration and motility in the stress group significantly decreased, and then sperm motility was improved by exercise in the stress+exercise group. In sum, our results show that chronic treadmill exercise may improve the adverse effects of chronic stress on sexual behavior and sperm parameters in male rats in terms of some parameters.
Keywords: Treadmill exercise; Restraint stress; Sexual behavior; Sperm parameters; Hormones